2014
DOI: 10.1002/ajpa.22502
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in human cranial trait scores: Effects of population, age, and body size

Abstract: Sex estimation from the skull is commonly performed by physical and forensic anthropologists using a five-trait scoring system developed by Walker. Despite the popularity of this method, validation studies evaluating its accuracy across a variety of samples are lacking. Furthermore, it remains unclear what other intrinsic or extrinsic variables are related to the expression of these traits. In this study, cranial trait scores and postcranial measurements were collected from four diverse population groups (U.S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
142
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(163 citation statements)
references
References 40 publications
18
142
1
2
Order By: Relevance
“…Additionally, the glabella, mastoid process, and nuchal crest contributed the highest proportional odds to the logistical regression formulae. Moreover, the glabella, mastoid process and nuchal crest showed the highest classification accuracies for all the groups, which is similar to findings from other studies [5,8,23]. The high and moderately high, positive polyserial correlations between the craniometric (e.g., mastoid height and basion-nasion length) and ordinal variables (e.g., mastoid and glabella) suggest a strong relationship between size and shape of the cranium (Tables 6-7), which corroborates findings from a North American study assessing the accuracy, correlation and corroboration of metric and nonmetric sex estimation [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the glabella, mastoid process, and nuchal crest contributed the highest proportional odds to the logistical regression formulae. Moreover, the glabella, mastoid process and nuchal crest showed the highest classification accuracies for all the groups, which is similar to findings from other studies [5,8,23]. The high and moderately high, positive polyserial correlations between the craniometric (e.g., mastoid height and basion-nasion length) and ordinal variables (e.g., mastoid and glabella) suggest a strong relationship between size and shape of the cranium (Tables 6-7), which corroborates findings from a North American study assessing the accuracy, correlation and corroboration of metric and nonmetric sex estimation [12].…”
Section: Discussionsupporting
confidence: 90%
“…Sexual dimorphism is population specific due to the differences in geographical location, as well as in the evolutionary influences and experiences of these groups [23,25,26]. Thus, the standards derived from the South African population increased overall classification accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on bones have shown that the performance of sex determination outside the reference population group for As evident from the past studies, skull is the most dimorphic and easily sexed portion of skeleton after pelvis, providing accuracy up to 94% [4][5][6][7]. Nevertheless, the two important parts, pelvis (95%) and skull (94%), are regarded as best indicators of sex identification in most situations owing to prominent dimorphic features in their architecture [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the two important parts, pelvis (95%) and skull (94%), are regarded as best indicators of sex identification in most situations owing to prominent dimorphic features in their architecture [4,7]. Commonly employed considerations in sex determination of skull are size differences and robusticity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation